PECULIARITIES OF STUDYING COMPLEX SENTENCES IN CLASSES ON RUSSIAN LANGUAGE OF BUSINESS DOCUMENTATION AND CULTURE OF SPEECH - Alibekova Rana Khudaiberdievna (Bright Mind Publishing, 2025)
This article highlights important aspects of studying complex sentences in the educational process of the Russian language in the direction of “business documents and speech culture”. Complex sentences are important not only as a grammatical unit, but also as an integral part of formal-stylistic speech. The author gives recommendations on the formation of speech culture in students based on effective methods, didactic materials and practical exercises used in the study of complex sentences in the classroom. The role of complex sentences in business documents and their style of expression are also analyzed.
Keywords: Russian language, complex sentences, business documents, speech culture, formal style, syntax, teaching methodology.